Surgical Outcome of Endoscopic Third Ventriculostomy in the Treatment of Obstructive Hydrocephalus - Rehman, Zia-Ur-; Ullah, Bashir; Aamir, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Hydrocephalus is the dilation of the cerebral ventricles, which can occur due to obstructed circulation of cerebrospinal fluid (CSF). In cases of communicative hydrocephalus, the blockage of cerebrospinal fluid circulation occurs due to a decrease in the absorption of CSF by the arachnoid granulations. On the other hand, non-communicating hydrocephalus is due to a blockage that occurs closer to the granulations, such as a narrowing of the aqueduct of Sylvius. Objective: To determine the surgical outcome in terms of success of ETV in obstructive hydrocephalus. Methods: Sixty-two patients presenting with obstructive hydrocephalus were treated with the ETV procedure over the period of one year. The success rate of ETV was determined. Results: Thirty-eight (61.3%) male and 24 (38.7%) female patients were treated for obstructive hydrocephalus. The mean age was 11.68±9.94 years. ETV was successful in 48 (77.4%) patients. Conclusion: ETV is an effective and efficient surgical treatment for obstructive hydrocephalus with a success rate of 77.4%.